Impact of low-cost air travel on tourism economy in Zadar County - Slobodan Ivanovic; Danijel Vucenovic; Suzana Baresa (UTMS Journal of Economics, 2014)
This paper aims to encompassingly show what impact low-cost airline companies have on the tourism business in Zadar County. The high cost of travel for tourists who choose to travel by airplane in the past two decades has been significantely lowered by low-cost airline companies such as Ryanair, Germanwings, Easyjet and others. Low-cost flights have ensured an increase in the number of flights, thus increasing the number of tourist visits to destinations connected to those flights. Zadar County has recognized the ability of low-cost flights to have potential for the development of tourism. Low-cost airline companies have reduced the negative balance of tourism economy. This study wishes to gather information on how much low-cost airline companies affect the increase of tourist ventures to Zadar County. Considering that the increase in number of tourist arrivals is directly linked to business revenue, it will also show how much they affect the economy in Zadar County tourism.
Keywords: R41; L83; 330; low-cost airline companies; Zadar County tourism; Zadar County tourist economy